'Women in Search of Justice', 1941 (pg. 2) (1941)
1941 1939-1945 "'Women in Search of Justice', 1941 (pg. 2)" [HFR0044b], 1941 This extract from Dorothy Elliott's unpublished autobiography, 'Women in Search of Justice', describes the setting up of the Ministry of Labour Women's Consultative Committee [WCC] and women munitions workers in the Royal Ordnance Factories.